Myelitis associated with glial fibrillary acidic protein IgG: characterization and comparison with aquaporin-4 IgG and myelin oligodendrocyte glycoprotein IgG myelitis - Yinyin Xie; Wanwan Zhang; Aoya Han; Wenlin Sun; Xinru Zhou; Yi Xie; Yunqing Ma; Yajun Lian; Cui Wang; Nanchang Xie (BMC Neurology)
Abstract Background Awareness of the characteristics of glial fibrillary acidic protein autoantibody (GFAP-IgG) associated myelitis facilitates early diagnosis and treatment. We explored features in GFAP-IgG myelitis and compared them with those in myelitis associated with aquaporin-4 IgG (AQP4-IgG) and myelin oligodendrocyte glycoprotein IgG (MOG-IgG). Methods We retrospectively reviewed data from patients with GFAP-IgG myelitis at the First Affiliated Hospital of Zhengzhou University and Henan Children’s Hospital from May 2018 to May 2023. AQP4-IgG and MOG-IgG myelitis patients served as controls. Results Thirty-four patients with GFAP-IgG myelitis were included (15 women, 12 children; median age at onset, 28.5 years). Over half experienced prodromal symptoms and required intensive care support. The median Expanded Disability Status Scale (EDSS) score was 4 at admission and 0 at final follow-up (median, 20 months). Cerebrospinal fluid (CSF) analysis showed markedly elevated leukocyte counts in 23 patients, elevated total protein in 28 patients, and decreased glucose levels in 9 patients. Longitudinally sagittal T2 and gadolinium-enhancing spinal cord lesions were detected. Features favoring GFAP-IgG over the other types included presence of fever and neck stiffness, requirement of intensive care and mechanical ventilation, higher monocyte-to-lymphocyte ratio (MLR), presence of hyponatremia, markedly elevated CSF leukocyte counts, increased CSF total protein levels, and decreased CSF glucose levels. Imaging findings more common in GFAP-IgG than in AQP4-IgG myelitis were longer diseased segments, central canal enhancement, and gadolinium-enhancing brain lesions. Higher EDSS scores at discharge distinguished GFAP-IgG from MOG-IgG. Conclusion Clinical, laboratory, imaging, and outcome variables facilitate differential diagnosis of myelitis subtypes.